2016
DOI: 10.1371/journal.pone.0162726
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Differential Diagnosis of Hidden Hearing Loss in Humans

Abstract: Recent work suggests that hair cells are not the most vulnerable elements in the inner ear; rather, it is the synapses between hair cells and cochlear nerve terminals that degenerate first in the aging or noise-exposed ear. This primary neural degeneration does not affect hearing thresholds, but likely contributes to problems understanding speech in difficult listening environments, and may be important in the generation of tinnitus and/or hyperacusis. To look for signs of cochlear synaptopathy in humans, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
543
7
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(598 citation statements)
references
References 51 publications
32
543
7
16
Order By: Relevance
“…Indeed, cochlear synaptopathy reduces the strength of auditory nerve responses; the auditory system then seems to respond by increasing some internal gain to amplify the weak response that remains (e.g., see Chambers et al, 2016). Based on these findings, one proposed method for identifying cochlear synaptopathy in humans computes the ratio of the summation potential (the response of the hair cells in the cochlea) to the action potential (the auditory nerve response; Liberman, Epstein, Cleveland, Wang, & Maison, 2016); however, neither this metric nor any other has yet been proven to be diagnostic of cochlear synaptopathy in humans (see comments in the section on Future Impact in the Clinic).…”
Section: Individuals Differ In Their Ability To Encode Fine Temporal mentioning
confidence: 99%
“…Indeed, cochlear synaptopathy reduces the strength of auditory nerve responses; the auditory system then seems to respond by increasing some internal gain to amplify the weak response that remains (e.g., see Chambers et al, 2016). Based on these findings, one proposed method for identifying cochlear synaptopathy in humans computes the ratio of the summation potential (the response of the hair cells in the cochlea) to the action potential (the auditory nerve response; Liberman, Epstein, Cleveland, Wang, & Maison, 2016); however, neither this metric nor any other has yet been proven to be diagnostic of cochlear synaptopathy in humans (see comments in the section on Future Impact in the Clinic).…”
Section: Individuals Differ In Their Ability To Encode Fine Temporal mentioning
confidence: 99%
“…In noiseexposed humans and animals, acoustic trauma (noise-induced hearing loss) leads to hair cell damage and causes a threshold shift [19,20]. Recent studies have indicated that ageing and/or moderate noise exposure can result in hidden hearing loss [21][22][23], which causes difficulties in speech discrimination and temporal processing in a noisy environment [24]. It can be detected physiologically, and is characterized by reduced amplitude in the sound-evoked spiral ganglion neuron activity (the first peak of the ABR waveform) [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…While CAP responses are, to date, typically used to extract the CAPs generated by sound in animal models, ear canal electrodes in humans are successfully used at this time to analyze deficits in auditory processing in subject groups who had normal audiometric thresholds up to 8 kHz [67] . Accordingly, CAPs were recorded in humans using tiptrodes inserted deep into the ear canal [67] .…”
Section: The Compound Ap Of the Auditory Nerve As A Biomarker To Detementioning
confidence: 99%